The Strategies Of Scavengers In Maintaining Their Viability Based On Social Networks In Surabaya City - M, Ita Kusuma; Hariadi, Sunarru Samsi; Hariadi, Sunarru Samsi; ., Subejo; ., Subejo; ., Mudiyono; ., Mudiyono (Advances in Social Sciences Research Journal, 2016)
As a big city, Surabaya still becomes its own magnetic attraction for the urban to come and earn a livelihood. The informal sector is basically a form of response to the migrants and the poor people of the city towards the uneven development in many regions. The informal sector operationally growing or developing in urban areas generally includes the fields of trade, construction, services, and transportation. And one of the types of work that can be categorized important is trading rubbish/garbage. The front-liners in trading rubbish/garbage are scavengers. Social network has its leading role in their effort to maintain the survival. It is very important to fulfill the need of information concerning employment, food, clothing, housing and others. Social network is formed because basically humans have their limitations in dealing with other people and the social network is used by scavengers as a strategy to maintain their survival. The study explored the ability of the scavengers in maintaining their viabilitybased approach to social network. This is a descriptive-qualitative research. The techniques applied were purposive and random samplings, data collection based on FGD, and in-depth interviews. After careful observation, it was known that the social network was formed due to the bond of kinship in the scavenger community. Besides the mechanical and organic ties of solidarity could develope a chain of trading to sell their scavenging goods. There was a mutual beneficial relationship between scavengers and collectors. They also developed their social interaction outside the communities. After some prudent observations were conducted, the strategies of scavengers in maintaining their viability based on social network were described. Keywords: strategy to maintain viability, scavengers, social network